Análise do isolamento sonoro de sistemas construtivos residenciais estruturados em aço - Danielly Borges Garcia (2004)
The appearing of residential construction systems in strutuctural with low cost steel comes followed of a preocupation in attending the minimum requeriments for user comfort, as well as aspects related to security, sustainability, durability and habitability. The present work approaches acoustic comfort proportioned by constructive systems,considering the analysis of restricted components that are proposed in the construction of pre-manufactured systems, since the reduction of mass and the assembly of light systems bring certainty over sound insulation of the environments. Some of the case studies consider systems practiced in laboratories, as well as systems practiced in loco, and are presented exclusively in this essay. Furthermore, this workalso presents an analysis on indices for sound insulation, practiced in others countries, offering specific recommendations for the insulation for construction that can be applied in Brasil.